Declining human activity intensity on alpine grasslands of the Tibetan Plateau. (15th October 2021) - Li, Meng; Zhang, Xianzhou; Wu, Jianshuang; Ding, Qiannan; Niu, Ben; He, Yongtao
Abstract: Climate change and human activities have profoundly changed the structure and functioning of alpine grassland ecosystems on the Tibetan Plateau, the most critical ecological safety shelter for Asia. However, it remains unclear to what degree human activity intensity has impacted the alpine grasslands of the Tibetan Plateau. Here we quantify human activity intensity on alpine grasslands of the Tibetan Plateau based on the relationship between actual and potential net primary production. We found that human activity intensity decreased by 16.1% from 2000 to 2017 across the alpine grasslands, which might be driven by recent ecological conservation policies, especially reductions in livestock numbers. Critical thresholds, which show marked grassland responses to different levels of human disturbances, were identified for each ecozone. The net primary production of dry grasslands on the western ecozones was more resistant to human disturbances but with lower resilience than other alpine grasslands on the plateau. Our findings are beneficial to design practical countermeasures to adapt to climate change and recover damaged grasslands on Tibetan Plateau. Highlights: The relationship between alpine grasslands productivity and climate factors were strengthening. Human activity intensity across alpine grasslands decreased by 16.1% on Tibetan Plateau. Thresholds quantifying alpine grassland response to human disturbance were identified.